Coil embolization of a ruptured gastroduodenal artery pseudoaneurysm presenting with hemosuccus pancreaticus - Naveed U. Saqib, MD, FACS; Hunter M. Ray, MD; Zain Al Rstum, MD; Joseph J. DuBose, MD; Ali Azizzadeh, MD; Hazim J. Safi, MD, FACS (Journal of Vascular Surgery Cases and Innovative Techniques, 2020)
Hemosuccus pancreaticus is a rare form of upper gastrointestinal bleeding that accounts for roughly 1 in 1500 cases. It is characterized by hemorrhage from the ampulla of Vater secondary to rupture of a peripancreatic pseudoaneurysm or visceral artery pseudoaneurysm. Among the visceral artery pseudoaneurysms, gastroduodenal artery pseudoaneurysms are among the rarest. In this case report, we describe a successful coil embolization of a large ruptured gastroduodenal pseudoaneurysm in a patient with massive gastrointestinal bleeding. Keywords: Hemosuccus pancreaticus, Visceral artery pseudoaneurysms, coil embolization